MEMBANGUN SEKOLAH BERKELANJUTAN: IMPLEMENTASI OPTIMALISASI SARANA PRASARANA DALAM SEKOLAH INKLUSI DAN ADIWIYATA - Nurahman; Prasetyaningrum, Eka; Minarni; Thea Kirana, Elika (Jurnal AbdiMas Nusa Mandiri, 2025)
Early childhood education in Kotawaringin Timur Regency faces several challenges, particularly in managing facilities and infrastructure. Many kindergartens and playgroups lack adequate resources, such as interactive classrooms and outdoor play areas, which limits children’s creativity and exploration. This condition requires teachers to be innovative in utilizing limited resources to create meaningful learning experiences. To address these issues, a community service program was conducted to enhance teachers’ knowledge and skills in optimizing school facilities to support sustainable learning. The program emphasized strategies for maximizing limited resources, fostering collaboration with parents, using social media, and integrating horticulture into the learning environment. Interactive training methods were employed, including presentations, discussions, and hands-on practice. A total of 94 participants from 47 educational institutions joined the program, recruited through collaboration with Himpaudi Kotim, IGRA, and PKG Markisa. The results showed that teachers gained new insights into maximizing existing facilities, strengthening parent communication via Instagram and WhatsApp, and applying horticulture as an engaging learning medium. The discussions also highlighted the relevance of these strategies to school quality improvement, including accreditation. In conclusion, this program provided practical solutions for optimizing educational facilities, supporting inclusive and Adiwiyata-oriented schools, and fostering stronger collaboration between schools, parents, and technology to achieve sustainable education.